Biomedical applications (chitin - chitosan) in tissue engineering - Leila Rezakhani; Tayebeh sadat Tabatabaei; Morteza Alizadeh (مجله دانشگاه علوم پزشکی گیلان)
Background: Tissue engineering is an important treatment strategy for the present and future medicine in the world. Objective: Recently, biomaterial research has led to the development beneficial and useful scaffolds for regenerative medicine. Methods:  In this study, the search for articles using the keywords chitin, chitosan, tissue engineering was carried out through a scientific search independently in Web of Science, Pubmed, Scopus, Science Direct and Google Scholar databases, and finally 94 articles were selected and reviewed. Results: Chitosan is a generic name for a group of chitin-acetyl compounds. This natural polymer is obtained from renewable sources such as oysters, crustaceans, and seafood waste. Chitosan scaffolds that have a porous structure are easily made by freezing and drying the chitosan solution. The polymer is used in the engineering of bone, cartilage, arteries, skin, and other tissues and can also be used to treat diseases such as cancer and the drug delivery system. In addition, the antioxidant and antimicrobial effects of this compound have led to its broader use in regenerative medicine. Conclusion: This review article reviews the general properties of chitosan and its various applications in tissue engineering.